Fibre devices enabled by hollow core fibre technology - Zang, Jichao (Nanyang Technological University, 2022)
The hollow-core photonic crystal fibres (HC-PCFs) are a newly developed branch of optical fibres with micro-structured cladding to confine a guided light, and they have appealed to a vast research interest for utilizing their distinguished properties of high material damage threshold, broad transmission bands, low confinement loss and little nonlinearity compared with the conventional solid fibres. The hollow-core anti-resonant fibres, as one category of the HC-PCFs, are specially featured by their ability of broad- band transmission and low interaction of a guided light and a cladding material. Up to now, there have been intensive studies focused on the guiding mechanism and background loss reduction in single hollow-core anti-resonant fibres (HAFs), and the HAFs have been explored in a wide range of applications including high power pulse delivery, nonlinear gas-light interactions, interferometric sensing, telecommunications networks, and optical fibre gyroscopes. The technological progress in the past has shown the readiness and ambitions of the technology for progression to device development. My motivation is to contribute to this exciting opportunity by exploring the HAF devices based on hollow-core anti-resonant fibres with both single and multiple hollow cores as possible fibre platforms to bring up the current transmission fibre to a fibre device level. Such technology progression is important to enabling hollow-core fibre-based all-fibre systems, contrasting today’s practice based on free-space optics due to the lack of hollow-core fibre components. Thus, my study is devoted to the exploration of hollow-core fibre devices, adopting designs of single- and multi-core HAFs, with post-drawing treatment when necessary. Inheriting all the advantages from standard single-core HAFs, novel HAFs with additional features are opening up new interesting properties, leading to applications such as fibre couplers, sensors and polarisers, and also addressing the current lack of fibre devices or components for future all-fibre integration. The scope of my Ph.D. work spans over fibre design, fabrication and characterisation of the multi- and single-core HAFs, to mimic solid core fibre-based devices in a hollow- core fibre platform, such as a coupler, a combiner, a sensor, and a polariser. The hollow core inherently offers material-unrestricted properties that today’s solid fibre devices cannot offer. In this thesis, the following work is demonstrated: the design, fabrication and characterisation of the structure of an air-gap triple-hollow-core anti-resonant fibre, which comprises three air cores and a cladding of two layers of glass capillaries; the building and experimental results of mechanical strain sensors based on single- and dual- hollow core anti-resonant fibres separately; the realisation and applications of an in-fibre polarizer based on HAF with asymmetrically designed structure. The in-house fabrications of all the utilized hollow-core fibres adopt the conventional stack-and-draw method. With further development, the HAFs can provide various functions, holding a promise for many more real-world applications.